Bacterial Infections in Patients with Liver Cirrhosis in an Internal Medicine Department - Gomes,Cristina Lameirão (2019)
Background and Aims: Liver cirrhosis (LC) is the end stage of multiple processes that lead to hepatic failure and is the 10th most common cause of death in the Western world. Bacterial infections are one of the most important clinical problems in patients with LC, as their underlying immune status is compromised. Approximately 60% of bacterial infections in cirrhotic patients are community acquired (CA) and 40% are nosocomial. The most common infections in cirrhotic patients are spontaneous bacterial peritonitis (SBP) (25%), urinary tract infection (UTI) (20%), pneumonia (15%), bacteremia (12%), and cellulitis (2-11%). The aim of this study was to evaluate the most frequent infections in patients with LC and describe the evolution of the microbiology in these patients. Material and Methods: This is a retrospective analysis of 4 interspersed years (2008, 2010, 2012, and 2014) that included 372 patients. Demographic characteristicswere evaluated, including gender, age, type of infection, bacteria resistance profile, antibiotic use, Child-Pugh-Turcotte and Model for End-Stage Liver Disease scores, and mortality rate. Results: The mean age of all patients enrolled in this study was 64.5 ± 12.2 years. Male patients were significantly more prevalent than female ones (72 vs. 28%). In the 4 analyzed years, the following numbers of infections occurred: 71 infections (49% CA and 51% nosocomial) in 2008; 86 infections (60.5% CA and 39.5% nosocomial) in 2010; 99 infections (56.6% CA and 43.4% nosocomial) in 2012; and 116 infections (70.7% CA and 29.3% nosocomial) in 2014. The most frequent infections were UTI (32.5%), respiratory tract infection (29.3%), SBP (26.1%), and cellulitis (6.2%). A microbiological agent was identified in 32.4, 59.3, 53.5, and 61.2% of infections in 2008, 2010, 2012, and 2014, respectively, with a predominance of gram-negative bacilli. In all series, a third-generation cephalosporin was the most frequent antibiotic used empirically. The majority of patients was in stage B (42.7%) of the Child-Pugh-Turcotte score, followed by stage C (39.3%) and stage A (18%). Mortality increased significantly over the years, from 7% in 2008 to 25% in 2014 (p = 0.016). Conclusions: The present study showed a high prevalence of bacterial infections in patients with LC. A high rate of suspicion is needed for an infectious process in these patients, and an appropriate antibiotic treatment can decrease the morbidity and mortality in cirrhotic patients.